2001
DOI: 10.1023/a:1012299021967
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Five candidate pheromone components were identified by analyzing pheromone gland extracts by gas chromatography (GC), coupled GC-electroantennographic detection (EAD), and coupled GC-mass spectrometry (MS) : (E)-11-hexadecenol(E11-16 : OH), (Z)-11-hexadecenol (Z11-16 : OH), (E)-11-hexadecenal, (E)-11-hexadecenyl acetate, and (Z)-3,(Z)-6,(Z)-9-tricosatriene (Z3,Z6,Z9-23 : Hy). In electroantennogram (EAG) recordings, synthetic E11-16 : OH elicited stronger antennal responses at low doses than other candidate phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Interestingly, the N. elegantalis female also secretes a Type I compound (E11-16:OH) like other Pyralidae species [55]. Only this species constructs a unique hybrid pheromone system that is composed of the Type I component biosynthesized de novo via a saturated fatty acid and the Type II component derived from dietary linolenic acid.…”
Section: Structures Of Pheromones In Type IImentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the N. elegantalis female also secretes a Type I compound (E11-16:OH) like other Pyralidae species [55]. Only this species constructs a unique hybrid pheromone system that is composed of the Type I component biosynthesized de novo via a saturated fatty acid and the Type II component derived from dietary linolenic acid.…”
Section: Structures Of Pheromones In Type IImentioning
confidence: 99%
“…1) [4][5][6][7]9]. Exceptionally, Z3,Z6,Z9-23:H has identified from one Pyralidae species, the tomato fruit borer (Neoleucinodes elegantalis, Crambinae) [55]. In this chapter, these Type II chemicals are abbreviated similarly to those of Type I; 'epo' and 'H' representing the cis-epoxy ring and the absence of a terminal functional group, respectively.…”
Section: Structures Of Pheromones In Type IImentioning
confidence: 99%
“…In this study, we proved that the OR14 mutants did not affect EAG response to three most important pheromone compounds (Figure 4), but it still has the possibilities to be activated by other chemicals. It has been reported that some lepidoptera moths use both type I and type II pheromones (Cabrera et al, 2001;Millar et al, 2005;Gibb et al, 2007), and PR can also be activated by both type of pheromones (Zhang and Löfstedt, 2013;Zhang et al, 2016). Therefore, OR14 may affect the recognition of this kind of pheromones.…”
Section: Discussionmentioning
confidence: 99%
“…8). 94 Among many other applications of GC-EAG to investigation of chemical communication in nature, of special importance are studies of the stereochemistry of pheromone with the use of chiral capillary gas chromatographic system. In these studies it was shown, however, that stereochemistry can only be unambiguously assigned by comparison of retention times and EAG responses of the natural and synthetic materials.…”
Section: Electrochemical Detection In Gcmentioning
confidence: 99%